2019
DOI: 10.1155/2019/3735427
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism of a Coal‐Rock Combined Body with Inclinations of Structural Planes and a Calculation Model for Impact Energy

Abstract: A coal-rock (CR) combined body can be used to simulate structures of coal and rock strata, and its impact-induced failure characteristic conforms more close to engineering practice. Exploring the mechanical properties and impact energy in a CR combined body contributes to better predictions of rock bursts in coal mines. In the study, the mechanical properties of CR combined bodies with four different inclinations (0°, 15°, 30°, and 45°) of structural planes were measured, and also their failure mechanism was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Zhao et al 9 studied and analyzed the peak strength, strain, and failure mode of the coal‐rock structural body with the different structural plane inclination angles and established the energy evolution computational model of the structural body. Dong et al 10 obtained the relationship between loading rate and peak strain, strength, and crack number.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al 9 studied and analyzed the peak strength, strain, and failure mode of the coal‐rock structural body with the different structural plane inclination angles and established the energy evolution computational model of the structural body. Dong et al 10 obtained the relationship between loading rate and peak strain, strength, and crack number.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of rock-to-coal strength ratio and height ratio on the impact trend, failure mode, and ultimate compressive strength characteristics of the composite sample have been analyzed thoroughly from a mesoscopic perspective [22]. Zhao et al analyzed the failure characteristics of CR (Coal Rock association) assemblies with various inclination angles (0 °, 15 °, 30 °, and 45 °), analyzed their failure mechanisms [23]. Wu et al conducted experiments on RCB specimens with different angles under different stress states, and found that the fracture tendency of RCB specimens increased with the increase of angle [24].…”
Section: Introductionmentioning
confidence: 99%